Construcción de una nueva escala en español para medir ansiedad. - Vega Dienstmaier, Johann (2013)
Objective: To construct a scale to evaluate the symptomatology of the different types of anxiety disorders. Materialand Method: After reviewing 25 instruments that assess nonspecific anxiety, generalized anxiety disorder (GAD),panic disorder, agoraphobia and other phobias, social phobia, obsessive-compulsive-disorder (OCD) and posttraumaticstress disorder (PTSD), new items were created and ordered according to the different types of anxiety symptomsand then on the frequency which its content appeared in the reviewed scales. Later, a scale was generated alternatingitems of different anxiety types beginning with the most frequent items of each category. Results: A new anxietyscale of 130 items was created (25 of nonspecific anxiety, 19 of GAD, 33 of panic disorder, agoraphobia and otherphobias, 29 of social phobia, 11 of OCD, and 13 of PTSD). Conclusions: This is the first step to create this newanxiety scale. Its application to healthy subjects and psychiatric patients with and without anxiety disorders toevaluate its psychometric features (factorial structure, internal consistency and validity), and later the modification,deletion and selection of items to generate a simpler and more useful scale, are pending.